Underutilisation of self-service libraries in Chinese cities: The absence of a patron-centric perspective. Issue 3 (19th September 2016) - Zhou, Lihong; Song, Yaqian; Zhou, Tong
Abstract : Purpose: Self-service libraries (SSLs) have been regarded as an effective approach to provide convenient book services to the enormously large populations of China's cities. These SSLs are in fact automatic book service machines, which provide a combination of services, including reading card issuing, book lending and returning, and book reservations and collection. However, despite acclaimed success, SSL services are not well received by patrons and are underutilised. The purpose of this paper is to identify and understand the causes of the underutilisation of SSL services in Chinese cities. Design/methodology/approach: This study adopted an inductive approach and a case study research design. The SSL services in Wuhan, the capital city of Hubei Province, were adopted as the case study, in which 20 public librarians, SSL workers and managers, and library patrons were approached and interviewed using semi-structured question scripts. The interview data were analysed using a thematic analysis approach. Findings: The analysis pointed to 13 causes in three main themes: management problems, service limitations, and the implicit role of government. Further conceptualisation of the findings revealed that the underutilisation of SSL services has resulted from the absence of a patron-centric perspective and the negligence of patrons' needs and requirements. Therefore, to increase the popularity and usage of SSLs, it is necessary to develop patron-centric management mechanisms through which patrons' needs and requirements can be effectively understood and responded to. Originality/value: This study aims to develop specific suggestions to improve the usage of SSLs. Furthermore, although this study focuses on SSL development in China, this research can provide useful suggestions and implications that can be shared across international borders.